Effect of personality on compound reasoning - Maria del Carmen Crivello; Eugenia Razumiejczyk; Guillermo Macbeth (Liberabit, 2020)
Objective: This study aims to describe the relationship between personality and propositional reasoning regarding compound negations by using, in particular, De Morgan’s laws. Method: To evaluate personality traits, we used the Adjective Checklist for Personality Assessment, an instrument based on the Big Five theory and developed for the Argentine context. To assess reasoning, we used a task implemented in previous studies, according to which subjects had to find the logical equivalent of a compound negation. Four response options were offered: one was correct and the other three were linked to specific biases. Both the research study and the paradigm were developed on the basis of the Mental Models Theory of Negation. The study had a correlational design and included 150 university students. Results: We found that factors such as neuroticism, extraversion, and agreeableness were linked to specific response patterns. Difficulty and context were considered mediators of the process. Discussion: The evidence was compatible with the Mental Models Theory but inconsistent with theories based on formal rules.